Impact of Macro Economic on Stock Return at BUMN Banking Period 2015-2022 - Maryati, Mari; Komala, Adeh Ratna; Andini, Rasyha; Irawati, Syakira Kiki (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The banking sector is one of the drivers of country’s economic growth, therefore the Indonesia Government always encourage and boosts the development of the banking sector, especially state-owned banks. To attract investment in the banking sector, the Indonesian government issued appropriate policies such as interest rate, maintaining inflation stability, and maintaining the exchange rate. This research aims to determine effect of inflation, exchange rate, and interest rate on stock return either partially and simultaneously. This sampling technique used in this research is purposive sampling with several criteria. While the analytical method used in this research using data panel regression. The results of this research inflation, exchange rate, and interest rate simultaneously and partially effect on stock return.